Feasibility and testing outcomes of task-shared implementation of advanced HIV disease point of care tests in Beira (Mozambique) and Kinshasa (DRC) - Zibusiso Ndlovu; Ruvimbo Nhandara; Kiyara Govender; Fingani Mpande-Nyasulu; Emmanuel Kabwe; Antonio Flores; Calorine Mekiedje; Laban Kyembe; Christine Bimansha; Tania Carmilla Tomas; Leticia Penna; Mariana da Silva; et al. (PLoS ONE, 2026)
Introduction Mortality from advanced HIV disease (AHD) remains high and current strategies to promptly test people eligible for AHD screening, are insufficient. Task sharing for point of care (POC) testing utilizing lay health workers (LHW) is recommended, however it is marginally practised in many countries. This study sought to describe the feasibility and testing outcomes of task-shared implementation of the AHD POC diagnostic tests utilizing LHW and professional health care workers (HCW). Methods This was a cross-sectional mixed-methods implementation study in seven primary and three secondary health facilities, in Mozambique and Democratic Republic of Congo (DRC). From March to November 2022, consenting HIV positive adults eligible for AHD screening, were offered Visitect CD4 lateral flow assay (LFA), and or subsequently urinary Mycobacterium tuberculosis lipoarabinomannan antigen (TB LAM) and cryptococcal antigen (CrAg) tests. The primary study outcome was the proportion of testers (LHW and HCW) who found it ‘easy’ to integrate the 3 POC tests within their routine work together with their opinions on the value of task shared AHD POC testing. Results A total of 1542 patients were screened for AHD by 35 LHW (34 counsellors, and 1 lay educator) and 45 professional HCW (28 nurses and 9 clinical officers and 8 doctors). In the study period, LHW conducted a median number of 27 [IQR: 16–34] Visitect CD4 LFA tests, whereas nurses, clinical officers together with doctors conducted 19 and 11 respectively. Visitect CD4 LFA increased CD4 testing by 10.7% in Munhava (Beira) and 22.9% in CHK (DRC), complementing existing CD4 testing instruments. Among testers who completed the feasibility survey, nearly sixty percent of testers (25/42; LHW in particular) found it easy to integrate AHD POC testing within their routine workflow. The prevalence of AHD was 39.2% (604/1542). A total of 34% (146/430) and 5.4% (22/407) of patients tested positive for urine TB LAM and plasma CrAg respectively. Of these, 82.2% (120/146) and 36.4% (8/22) had a documented therapeutic intervention. The median time for completing the Visitect CD4 LFA and conveying the results to the clinician was 59 minutes [IQR: 48–71]. Conclusion Task-shared integrated testing for AHD at POC among LHW and professional HCW, is feasible and can improve access to AHD testing. However, as POC testing responsibilities become shared, documentation of testing activities could increase in complexity and can be easily fragmented, especially when there is limited supervision. Nevertheless, LHW are well suited for POC testing due to limited availability and higher clinical workload of other HCW.